CARDIOMETABOLIC STRATEGIES IN HEART FAILURE AND CHRONIC KIDNEY DISEASE: FROM GLP-1 RECEPTOR AGONISTS TO IMPROVED QUALITY OF LIFE AND TECHNOLOGY-ENABLED CARE - Daria Sztefka; Agata Jaunich; Katarzyna Szlachetka; Adam Zając (International Journal of Innovative Technologies in Social Science, 2026)
Heart failure (HF) and chronic kidney disease (CKD) frequently coexist and interact in a way that worsens prognosis, increases hospitalization risk, and reduces quality of life. This overlap is increasingly understood within the cardiovascular-kidney-metabolic (CKM) framework, which recognizes obesity, insulin resistance, type 2 diabetes, kidney dysfunction, and cardiovascular disease as interconnected components of a shared pathophysiological continuum rather than isolated disorders. In this context, glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have attracted growing clinical interest because their actions extend beyond glycemic control and include body weight reduction, metabolic improvement, and favorable effects on selected cardiovascular and renal outcomes. The aim of this narrative review is to summarize the current evidence on GLP-1-based therapies in patients with HF and CKD, with particular emphasis on semaglutide, liraglutide, and tirzepatide. The review focuses on biological rationale, major clinical trials, practical implications, and the emerging role of precision phenotyping, digital health, wearable monitoring, and artificial intelligence in long-term CKM care. The structure of the review was informed by general scoping review principles, although it was not designed as a formal systematic review or meta-analysis. Available evidence suggests that GLP-1-based therapies may offer clinically meaningful benefits, particularly in patients with obesity, type 2 diabetes, HF with preserved ejection fraction (HFpEF), and CKD. Semaglutide has shown the strongest and most consistent evidence, improving symptoms, physical limitations, exercise capacity, and body weight in obesity-related HFpEF, while also reducing clinically important kidney outcomes in patients with CKD and type 2 diabetes. Liraglutide remains historically important because it helped establish cardiovascular benefit for the GLP-1 RA class, whereas tirzepatide represents a promising next-generation option in patients with a marked metabolic phenotype and obesity-related HFpEF. In conclusion, GLP-1-based therapies are becoming an important component of modern CKM care. Their relevance extends beyond glucose lowering and includes symptom improvement, better physical functioning, cardiovascular risk reduction, and kidney protection in selected populations. Future progress in this field will likely depend on more precise patient selection, better integration with existing cardiorenal therapies, and wider use of digital and phenotype-guided approaches to support individualized long-term care.